Peran Kerjasama antara Travel An-Nur Maarif Parepare dan Bank Syariah terhadap Peningkatan Jumlah Jama’ah - Kartika Sabir; Syahriyah Semaun; Ade Hastuti (Institut Agama Islam Negeri Parepare, 2020)
This research is to find out the system of cooperation between Travel and Islamic Banks in PT. An-Nur Maarif Parepare. And to find out how much an increase in the number of PT. An-Nur Maarif Parepare after cooperation with Islamic Bank.This type of research used in this thesis is a qualitative descriptive method, the data in this study were obtained from primary data and secondary data. Data collection techniques used were observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions.The results of this study indicate that: 1). Cooperation system between PT. An-Nur Maarif and Sharia Bank in Hajj and Umrah are promotion, trust and service. The system of cooperation carried out in terms of promotion is the public financing. PT. An-Nur Maarif in building the trust of congregants and the community is to bring partners from the Islamic Bank in activities such as rituals. In addition to building and increasing the trust of the congregation, providing the best service to the congregation is also very important because if the congregation has felt the quality of service according to expectations can lead to a positive story from the congregation and it certainly will greatly affect travel and work partners because of the loyalty of the congregation can even attract prospective congregations. 2). Increasing the number of pilgrims depends on the services of the travel. One of the services provided by PT. An-Nur Maarif is collaborating with Islamic banks on funding. With the cooperation carried out by PT. An-Nur Maarif with Sharia Bank can be said to run well with evidence that the congregation has increased every year